On the manufacturability of scaffold mould using a 3D printing technology - Liu, C; Sachlos, E; Wahl, D; Han, Z; Czernuszka, J (2007)
Purpose: To investigate the effect of operation parameters and printing configuration on the manufacturability of moulds in the manufacture of tissue engineering scaffolds using a 3D printing system. Design/methodology/approach: The scaffold moulds were built using proprietary biocompatible materials using a modified Solidscape T66 ink-jet printing system. The manufacturability of biological scaffold moulds has been investigated in terms of resolution, accuracy, and minimum and maximum manufacturable features. Findings: The results demonstrated that the 3D system used in this study is able to fabricate structures with high reproducibility and flexibility. It was found that thermal degradation of BioSupport material had an adverse effect on resolution and accuracy of moulds printed for scaffold manufacturing. The maximum features, including maximum length and height, are geometrical dimension and orientation dependent. The system could produce a longer and higher features when the mould was aligned perpendicular to the axis of the mill than that parallel to the axis of the mill. The bigger the cross-sectional area, the longer/higher the manufacturable feature the machine can produce. The accuracy and resolution are attributed to the size of the molten droplet of BioBuild that caused local melting of the support layer and which partially diffused into the support layer. Research limitations/implications: The results provide a guide to the design and fabrication of precision scaffold for tissue engineering using biocompatible materials. Originality/value: This paper describes a method and process to evaluate the manufacturability of a scaffold mould using 3D printing technique. The limits to mould design are established, it could be extended to other solid freeform fabrication systems for effective operation and precision control. © Emerald Group Publishing Limited.